(untitled) (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2024)
Purpose: To analyze the impact of Procurement practice adopted on budgetary utilization with a case of Mandandeupur Municipality, newly formed municipality in Kavrepalanchowk district under Bagmati province of Nepal. Design/Methodology/Approach: A structured set of questionnaires were developed in order to analyze the impact of Procurement practice adopted on budgetary utilization with a case of Mandandeupur Municipality, newly formed municipality in Kavrepalanchowk district under Bagmati province of Nepal through regression and chi-square. Findings/Result: The relation between the number of bidders and budget utilization was found to be not correlated, below the engineer’s estimate. And budget utilization was found to be strongly correlated; engineer’s estimate and budget utilization were found to be significantly correlated; and the combined relation of the number of bidders below engineer’s estimate, engineer’s estimate and budget utilization was found to be significant, whereas below engineer’s estimate was most significant. The contract administration part of the contract seemed to be weak in the parts of safety and plan and strong in the case of document management. The contract administration of large budget contracts seems to follow the process, whereas projects with a small budget seem to skip the process of contract administration. Originality/Value: The pragmatic recommendations can help improve the budget utilization trend analysis and contract administration practices at the local level, leading to more effective and efficient implementation of development projects. Paper Type: Empirical Research